2019
DOI: 10.31557/apjcp.2019.20.12.3763
|View full text |Cite
|
Sign up to set email alerts
|

AMPK Activation of Apoptotic Markers in Human Breast Cancer Cell Lines with Different p53 Backgrounds: MCF-7, MDA-MB-231 and T47D Cells

Abstract: Background: Downregulation of AMPK has been established as a major contributor to carcinogenesis in many types of human cancer. We sought to investigate the influence of activated AMPK on apoptotic markers in human breast cancer cells differing in their p53 status, as well as estrogen receptor status (MCF-7 (p53+ and ER+), MDA-MB-231 (p53 mutant and ER-) and T47D (p53 mutant and ER+)). Methods: We examined the effect of AICAR-activated AMPK on PARP cleavage, Bax redistribution, the involvement of intrinsic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Therefore, further studies on antiestrogen therapy accompanied by TGZ treatment should be undertaken as an approach to experimental therapy of ER negative breast cancer cells. Downregulation of AMPK, metabolic regulator involved in control of cell growth and survival has been established as a major contributor to carcinogenesis in many types of human cancer [51]. We have found that TGZ induced in dose-dependent manner AMPK expression.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Therefore, further studies on antiestrogen therapy accompanied by TGZ treatment should be undertaken as an approach to experimental therapy of ER negative breast cancer cells. Downregulation of AMPK, metabolic regulator involved in control of cell growth and survival has been established as a major contributor to carcinogenesis in many types of human cancer [51]. We have found that TGZ induced in dose-dependent manner AMPK expression.…”
Section: Discussionmentioning
confidence: 75%
“…Although the mechanism is not well understood, the activation of p53 in the cells cultured in estradiol-free medium is supported by some other authors, suggesting that estradiol inactivates P53 [54] or estrogen receptor prevents p53-dependent apoptosis in breast cancer [55,56]. It seems that in the absence of estradiol, TGZ-treated MCF-7 cells may undergo apoptosis by p53 signaling [50,51], while MDA-MB-231 cells, due to p53 mutation, through PRODH/POXdependent ROS generation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…AMPK, a crucial cellular energy sensor regulating metabolic processes 39 , has been reported as a novel tumor suppressor in various cancers 40 . Moreover, the activation of p-AMPK was associated with ER stress, which led to cells death 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the activation of p-AMPK was associated with ER stress, which led to cells death 43 . Studies have shown that metformin can enhance the anti-cancer effect of dasatinib mainly through p-AMPK mediated ER stress 40 . Consecutively, in our study, whether p-AMPK/p-ACC involved in regulating anti-cancer by DIM-mediated ER stress is added.…”
Section: Discussionmentioning
confidence: 99%